1986
DOI: 10.1007/bf00973742
|View full text |Cite
|
Sign up to set email alerts
|

Long-term persistence of two-year college students

Abstract: This paper employed a theoretical model to explain the long-ter persistence of students who began their post-secondary education in two-year institutions. The model waa estimated on a national sample of 825 students who initially enrolled in 85 two-year institutions in the fall of 1971, and were followed over a nine-year period.Although there were differences in the factors associated with persistence for men and women, the results tend to confirm the importance of person-environment tit as a salient influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
114
2
18

Year Published

1993
1993
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(143 citation statements)
references
References 19 publications
9
114
2
18
Order By: Relevance
“…Estos estudios indican que si bien la integración social y académica son factores importantes para predecir la persistencia, no tienen la misma importancia en todos los estudiantes. anderson (1981), Braxton y Brier (1989), Pascarella y chapman (1983aPascarella y chapman ( , 1983b y Pascarella et al (1986), Pascarella y terenzini (1985) reportaron que la integración académica es más fuerte que los compromisos o metas institucionales; por tanto, los compromisos institucionales tienen un efecto indirecto sobre la permanencia a través de la integración social 5 .…”
Section: Modelos Económicos Según Las Investigaciones Desarrolladas unclassified
“…Estos estudios indican que si bien la integración social y académica son factores importantes para predecir la persistencia, no tienen la misma importancia en todos los estudiantes. anderson (1981), Braxton y Brier (1989), Pascarella y chapman (1983aPascarella y chapman ( , 1983b y Pascarella et al (1986), Pascarella y terenzini (1985) reportaron que la integración académica es más fuerte que los compromisos o metas institucionales; por tanto, los compromisos institucionales tienen un efecto indirecto sobre la permanencia a través de la integración social 5 .…”
Section: Modelos Económicos Según Las Investigaciones Desarrolladas unclassified
“…After Bean and Metzner's publication in 1985, other studies began to apply Tinto's model to community college institutions (Baird, 1991;Bers & Smith, 1991;Borglum & Kubala, 2000;Boughan, 1998;Goel, 2002;Grosset 1989Grosset , 1991Halpin, 1990;Karp, Hughes, & O'Gara, 2008;Mutter, 1992;Napoli & Wortman, 1996Nippert, 2000Nippert, -2001Nora, 1987;Pascarella, Smart, & Ethington, 1986;Sorey & Duggan, 2008;Strauss & Volkwein, 2005;Townsend & Wilson, 2006Voorhees, 1987;Webb, 1988Webb, , 1989. Many studies found that only academic integration affected student persistence at community colleges (Baird, 1991;Fox, 1986;Goel, 2002;Grosset, 1991;Haplin, 1990;Mulligan & Hennessy, 1990;Mutter, 1992;Nippert, 2000Nippert, -2001Nora, Attinasi, & Matonak, 1990;Webb, 1988).…”
Section: Tinto and Community Collegesmentioning
confidence: 99%
“…Boughan, 1998;Goel, 2002;Grosset 1989Grosset ,1991Halpin, 1990;Karp, Hughes, & Q'Gara, 2008;Mutter, 1992;Napoli & Wortman, 1996Nippert, 2000Nippert, -2001Nora, 1987;Pascarella, Smart, & Ethington, 1986;Sorey & Duggan, 2008;Strauss & Volkwein, 2005;Townsend & Wilson, 2006Voorhees, 1987;Webb, 1988Webb, , 1989. In 1982, Tinto noted that his original model "is not very sensitive to forms of disengagement that occur within the two-year college sector (p.689).…”
Section: Tinto's Model and Community Collegesmentioning
confidence: 99%
See 2 more Smart Citations